Emergency Preparedness in Healthcare Systems: A Health Security Framework for Risk Assessment, Resilience, and Continuity of Operations - Alotaibi, Turki Muqbil Marzouq; Rawan Mohammed Ali Al-Qahtani; Bashayr Thear Mesfer Alqahtani; Tahani Hadi Yahya Aati; Naif Abdulaziz Hathal Aldawsari; Muneerah Saleh Sulman Alshunaifi; Thamer Mohsen Mohammed Aldajani; Sarah Mohammed Nasser Alshuhail; Mashail Ibrahim Jaza AlQahtani; Mohammed Ayad Nasir Alqahtani; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Healthcare systems face increasing threats from natural and man-made disasters, requiring robust emergency preparedness frameworks to ensure continuity of operations and protect public health. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This study aims to develop a comprehensive health security framework for risk assessment, resilience, and continuity of operations, with a focus on pediatric emergency readiness and interprofessional interventions. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review approach was employed, synthesizing disaster management literature, international guidelines, and evidence-based frameworks such as SMAUG for risk prioritization. The analysis included disaster typologies, operational classifications, and preparedness strategies across healthcare systems. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Findings highlight that preparedness is a dynamic, systems-based process requiring clear terminology, hazard classification, and adaptive planning. Pediatric emergency readiness emerged as a critical determinant of clinical outcomes, with significant gaps identified in general emergency departments. Interprofessional collaboration, technology integration, and continuous training were found essential for operational resilience. Frameworks like SMAUG support transparent prioritization, while drills and exercises ensure practical capability. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Emergency preparedness in healthcare must integrate risk assessment, pediatric readiness, and interprofessional coordination into continuous planning cycles. Leadership commitment, interoperability, and sustained training are vital for resilience. Benchmarking against international standards can transform preparedness from aspirational to operational, reducing morbidity and mortality during crises.